Efficacy and safety of BAY 81‐8973, a full‐length recombinant factor VIII: results from the LEOPOLD I trial. (24th June 2016) - Saxena, K.; Lalezari, S.; Oldenburg, J.; Tseneklidou‐Stoeter, D.; Beckmann, H.; Yoon, M.; Maas Enriquez, M.
Abstract : Introduction: BAY 81‐8973 (Kovaltry ® ) is a full‐length, unmodified recombinant human factor VIII (FVIII) with the same amino acid sequence as sucrose‐formulated recombinant FVIII and is produced using additional advanced manufacturing technologies. Aim: To demonstrate efficacy and safety of BAY 81‐8973 for treatment of bleeds and as prophylaxis based on two different potency assignments. Methods: In LEOPOLD I (ClinicalTrials.gov identifier, NCT01029340), males aged 12–65 years with severe haemophilia A and ≥150 exposure days received BAY 81‐8973 20–50 IU kg −1 two or three times per week for 12 months. Potency was based on chromogenic substrate assay per European Pharmacopoeia and label adjusted to mimic one‐stage assay potency. Patients were randomized for potency sequence and crossed over potency groups after 6 months, followed by an optional 12‐month extension. Primary efficacy endpoint was annualized bleeding rate (ABR). Patients also received BAY 81‐8973 during major surgeries. Results: Sixty‐two patients received BAY 81‐8973 prophylaxis and were included in the analysis. Median ABR was 1.0 (quartile 1, 0; quartile 3, 5.1) without clinically relevant differences between potency periods. Median ABR was similar for twice‐weekly vs. three times‐weekly dosing (1.0 vs. 2.0). Haemostasis was maintained during 12 major surgeries. Treatment‐related adverse event (AE) incidence was ≤7% overall; no patient developed inhibitors. One patient with risk factors for cardiovascular disease developed a myocardial infarction. Conclusions: BAY 81‐8973 was efficacious in preventing and treating bleeding episodes, irrespective of the potency assignment method, with few treatment‐related AEs. Caution should be used when treating older patients with cardiovascular risk factors.